Mobilisation de femmes chinoises migrantes se prostituant à Paris. De l’invisibilité à l’action collective - Hélène Le Bail (Genre, Sexualité et Société)
Almost invisible in the Parisian urban landscape a few years ago, the Chinese sex workers have attracted lots of attention since 2013 due to their involvement in the recent demonstrations against a new bill on sex work. Since then, the Chinese women, mostly irregular residents, were invited by elected representatives on local and national level and they created a sex worker collective at the end of 2014. To explain the rallying of highly stigmatized and precarious migrant women, three factors can be studied. Firstly, those women share a collective identity based on a common migration experience which is highly stigmatized. Secondly, they have the support of a well-established NGO which mobilized practical, political and media resources for them. Thirdly, their mobilization took place in a period of legislative reform and of broader mobilization among sex workers’ groups, which was a window of opportunity. The article proposes a chronological account of the mobilization process which underlines the synergy between the quest of legitimacy by the Chinese migrants and the militant approach of a humanitarian NGO, Doctors of the World.